2D argyrodite LPSCl solid electrolyte for all-solid-state Li-ion battery using reduced graphene oxide template. (January 2022) - Kang, Seok Hun; Kim, Ju Young; Shin, Dong Ok; Lee, Myeong Ju; Lee, Young-Gi
Abstract: All-solid-state lithium-ion batteries (ASLBs) are regarded as the next generation of energy storage devices owing to their excellent safety. However, the performance of ASLBs has yet to reach that of currently commercialized liquid electrolyte-based lithium-ion batteries due to numerous problems, including the inferior ionic conductivities of solid electrolytes (SEs) and poor solid-solid interfacial contact between the SE and active material particles. Herein, dimensional control of SE particles using liquid-phase synthesis is demonstrated and its favorable impact on cell performance is investigated. Argyrodite Li6 PS5 Cl SE with high ionic conductivity of 1.54 mS cm −1 and distinct 2D morphology was synthesized using 2D structured reduced graphene oxide as the template. The SE particles with a high aspect ratio improve the long-range connectivity of the SE within the composite electrode and provide a well-connected ionic transport pathway for charge-discharge. The electrochemical impedance spectroscopy analysis of the composite electrode using electron blocking cell configuration revealed a threefold enhancement of the effective ionic transport within the composite. As a result, superior rate performance was demonstrated with 2D SE composite electrodes at high C rates. Graphical abstract: Image 1 Highlights: Argyrodite Li6 PS5 Cl solid electrolyte with 2D morphology was synthesized. High ionic conductivity was achieved with a scalable liquid-phase technique. 2D morphology improves the ionic conduction within the composite electrode. All-solid-state lithium-ion battery with enhanced rate performance was demonstrated.